2018
DOI: 10.3390/ijms19061727
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Identification and Characterization of Warming-Related Genes in Brassica rapa ssp. pekinensis

Abstract: For sustainable crop cultivation in the face of global warming, it is important to unravel the genetic mechanisms underlying plant adaptation to a warming climate and apply this information to breeding. Thermomorphogenesis and ambient temperature signaling pathways have been well studied in model plants, but little information is available for vegetable crops. Here, we investigated genes responsive to warming conditions from two Brassica rapa inbred lines with different geographic origins: subtropical (Kenshin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 58 publications
0
2
0
Order By: Relevance
“…However, we found that the B. rapa FT.a locus showed increased H2A.Z levels at high ambient temperature compared with 21°C (Figures c and S5). To determine if this effect was specific for FT.a or may reflect a more general response to the heat stimulus, we studied some genes previously shown to be misexpressed by heat stress in B. rapa (Dong et al ., ; Song et al ., ). We found that BraA.HSP23 , BraA.HSP18 and BraA.bHLH expression was clearly upregulated, whereas BraA.SOB5 and BraA.GRSX expression was downregulated at 28°C compared with 21°C in B. rapa leaves (Figure a,b).…”
Section: Resultsmentioning
confidence: 97%
“…However, we found that the B. rapa FT.a locus showed increased H2A.Z levels at high ambient temperature compared with 21°C (Figures c and S5). To determine if this effect was specific for FT.a or may reflect a more general response to the heat stimulus, we studied some genes previously shown to be misexpressed by heat stress in B. rapa (Dong et al ., ; Song et al ., ). We found that BraA.HSP23 , BraA.HSP18 and BraA.bHLH expression was clearly upregulated, whereas BraA.SOB5 and BraA.GRSX expression was downregulated at 28°C compared with 21°C in B. rapa leaves (Figure a,b).…”
Section: Resultsmentioning
confidence: 97%
“…31 After recombinant expression of the Bacillus subtilis antifungal gene sequence Mt330, the Fusarium graminearum mycelial growth rate and biomass were reduced, while the intracellular BCAA pathway was significantly affected. 32 The addition of L-Ile and L-Pro significantly promotes F. oxysporum spore formation when the TORC1-Tap42 signaling pathway is inhibited. 33 Fu et al mentioned that arginine and proline metabolisms are closely related to the pathogenicity of fungi.…”
Section: ■ Results and Discussionmentioning
confidence: 98%